Optimization of transportation problem using linear programming technique / Haydar Hadzori - Hadzori, Haydar (2019)
Optimization is using available resources in the best possible way. Whether the objective is to maximize profit or minimize cost, optimization of a problem can lead to better planning for an organization. Mathematical tools such as Linear Programming allow such optimization problem to be modeled mathematically to solve it. In this paper, linear programming was used to solve the optimization for transportation problem that involves transporting rice from Padiberas Nasional Berhad (PNB) rice mills to wholesalers and customers in Malaysia. PNB currently deliver rice from five rice mill to 22 different locations in the eight state of Malaysia. Since not all destinations involved in the transportation process, the right amount of rice that should be transport to each destination is important for the company to utilize available resource in the best way. This paper aimed to minimize total transportation cost that was incurred by the company. It also discussed the sensitivity analysis impact of changes in cost incurred at each rice mill to its destination toward the total transportation cost. POM-QM for Windows was used to solve the model for minimization of total transportation cost. The result show that total transportation cost was able to be minimized from RM 3,010,895 to RM 2,187,310.30.